The Moderating Role of Leverage on Capital Intensity on Accounting Conservatism - Aprilia, Ferlis; Azis, Azolla Degita; Prasetya, Angga; Rumiasih, N.A (Jurnal Mahasiswa Akuntansi dan Bisnis (JMAB), 2024)
This research aims to examine the moderating role of leverage on capital intensity in relation to accounting conservatism. Using SPSS 26 and the purposive sampling method, this research focuses on manufacturing companies in the consumer goods and agricultural sectors listed on the Indonesia Stock Exchange (BEI) during the 2019-2022 period. The results show that capital intensity has a positive effect on accounting conservatism, while leverage has a negative effect. This means that the higher the capital intensity, the more conservative the company's financial statements, while companies with high leverage tend to be less conservative. Furthermore, Leverage does not moderate the relationship between capital intensity and accounting conservatism. These findings provide practical implications for manufacturing companies, investors, and regulators. Companies should consider capital intensity and leverage in conservative accounting policies. Investors can leverage this information for better decision making, and regulators can use these results to promote transparency in the manufacturing sector. This research also opens up opportunities for further study on other factors that influence accounting conservatism.